Rethinking school feeding: Social safety nets, child development, and the education sector - Bundy, Donald A. P; u.a (Directions in development, 2009)
This review was prepared jointly by the World Bank Group and the World Food Programme (WFP), building on the comparative advantages of both organizations. It examines the evidence base for school feeding programs with the objective of better understanding how to develop and implement effective school feeding programs in two contexts: a productive safety net, as part of the response to the social shocks of the global food, fuel and financial crises, and a fiscally sustainable investment in human capital, as part of long-term global efforts to achieve Education for All and provide social protection to the poor.